Zeitoun eaudiobook - Eggers, Dave (Recorded Books, 2009)
Dave Eggers is the New York Times best-selling author of the critically lauded A Heartbreaking Work of Staggering Genius. Here he chronicles the Kafka-esque tribulations of Syrian-American Abdulrahman Zeitoun in the wake of Hurricane Katrina. His story is a moving testament to the resilience of the human spirit. "This is a beautiful book. Zeitoun is a poignant, haunting, ethereal story about New Orleans in peril." -Douglas Brinkley, New York Times best-selling author